An Analysis Of The Factors Affecting Land Value (A Case Study At Campus Area On Jalan Williem Iskandar Medan) - Danu Wijaya; Sukaria Sinulingga; Khaira Amalia F (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
A campus construction requires wide land space. It indirectly attracts people from out of town to settle around campus area for various advantageous reasons. These settlers create a variety of demands which directly and indirectly bring impacts on the increase in land demands. This causes an assumption that the land value around campus area is higher that of outside campus area. Jalan Williem Iskandar Medan is one of the streets which area can be classified into campus areas. The objective of the study was to analyze the influence of factors such as surface area, land distance from the closest campus, land form, width and contour on the land value around campus on Jalan Williem Iskandar Medan. The study applied multiple regression analysis using questionnaire data. The samples were determined by using Unrestricted Random Sampling Method which drew the samples directly from the population. This study used 86 samples distributed in the population area covering 2 (two) locations i.e. Komplek Citra Land Bagya City and Komplek Mutiara Palace Residence. It focused on the identification of the influence of factors such as surface area, land distance from the closest campus, land form, width and contour on the land value in housing complexes particularly in Komplek Citra Land Bagya City and Komplek Mutiara Palace Residence located in the campus area on Jalan Williem Iskandar Medan. The results showed that on alpha 5%, the variables such as surface area, land distance from the closest campus, land width, form and contour had positive and significant influence on the land value. Based on these results, it could be concluded that independent variables such as surface area, land distance from the closest campus, land form, width and contour simultaneously were able to describe the changes on the dependent variables such as land value, and they had significant influence on land value.